1994
DOI: 10.1016/s0741-5214(94)70124-5
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating atherosclerotic ulcers of the aorta

Abstract: This study investigates the natural history and optimal imaging modality of penetrating atherosclerotic ulcers of the aorta. Methods: We reviewed our experience with 29 penetrating ulcers in 18 patients. Computed tomography (17 patients), magnetic resonance imaging (nine patients), and aortography (five patients) were used for diagnosis and follow-up. Patients were typically elderly (average age 74 years) and had hypertension and coronary artery disease. Ulcers were most common in the distal descending thoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
2
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(144 citation statements)
references
References 14 publications
5
133
2
4
Order By: Relevance
“…Stanson et al 2 and Coady et al 7 found PAUs to be malignant, but most of these patients had acute symptoms. In contrast, Harris et al 16 and Quint et al 17 reported a lower incidence of life-threatening complications in a patient sample where asymptomatic patients were enrolled. The considerable difference in prognosis probably can be explained by the differences in patient substrate (symptomatic versus asymptomatic).…”
Section: Natural History Of Paumentioning
confidence: 89%
“…Stanson et al 2 and Coady et al 7 found PAUs to be malignant, but most of these patients had acute symptoms. In contrast, Harris et al 16 and Quint et al 17 reported a lower incidence of life-threatening complications in a patient sample where asymptomatic patients were enrolled. The considerable difference in prognosis probably can be explained by the differences in patient substrate (symptomatic versus asymptomatic).…”
Section: Natural History Of Paumentioning
confidence: 89%
“…The prototype of this lesion may be an ulcer-like lesion. [8][9][10][11] Cystic medial necrosis was observed in the non-dissecting segment of the aorta of Case 1 and this degeneration might be the underlying abnormality of these lesions, although its significance in dissection is controversial. [12][13][14][15][16][17][18] Marsalese, et al 19) reported that 53% of patients with cystic medial necrosis died of aortic dissection or rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating aortic ulcers rarely lead to transmural rupture of the aorta, [5][6] and no papers showing a penetrating aortic ulcer complicated with an extra-aortic hematoma were found. However, Coady, et al 7) found that intramural hematomas had higher rupture rates than classic aortic dissections, probably because the level of blood collection is more superficial and closer to the adventitia than that of aortic dissection.…”
Section: Discussionmentioning
confidence: 99%